2020
DOI: 10.1097/sap.0000000000002525
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment of Posttraumatic Lymphedema by Soft Tissue Reconstruction With Lymphatic Vessels Free Flap

Abstract: Background Extremities soft tissue damage may increase the risk of presenting posttraumatic lymphedema. This type of lymphedema is often ignored in trauma and reconstructive literature. We propose a microsurgical soft tissue reconstruction approach to prevent and/or treat posttraumatic lymphedema. Patients and Methods This is a multicentric retrospective observational study. Primary and secondary end points were to prevent and/or treat posttraumatic lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Only few studies reported about the occurrence of this highly relevant issue in trauma patients. For example, Pereira et al performed SCIP lymphatic vessel transfer in patients with secondary lymphedema after trauma, and furthermore were able to surgically prevent development of secondary lymphedema after soft tissue injury in a small patient cohort [10,11]. However, no information was given about the prevalence of secondary lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies reported about the occurrence of this highly relevant issue in trauma patients. For example, Pereira et al performed SCIP lymphatic vessel transfer in patients with secondary lymphedema after trauma, and furthermore were able to surgically prevent development of secondary lymphedema after soft tissue injury in a small patient cohort [10,11]. However, no information was given about the prevalence of secondary lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic lymphedema is an ignored complication from extremity injury and a subtype of secondary lymphedema. According to a previous report, up to 20% of patients with traumatic injuries of the extremities involving bone fracture and soft tissue trauma experience persistent edema after the acute event (Pereira et al, 2019;Pereira et al, 2021). Based on the high incidence, the demand of lymphedema treatment is high.…”
Section: Introductionmentioning
confidence: 99%
“…Acute edema to some degree is expected with musculoskeletal trauma. However, persistent swelling after mechanical insult diagnosed as lymphedema has been reported following a wide variety of insults and in a variety of anatomic regions [3,[13][14][15] . Unsurprisingly, extensive injuries such as limb amputation with replantation have been reported to cause secondary lymphedema [16] .…”
Section: Musculoskeletal Injuriesmentioning
confidence: 99%
“…In the second report, the patient's fracture was treated operatively with open reduction and internal fixation. Persistent ipsilateral swelling was noted immediately after cast removal, and at two months postoperatively, the patient was diagnosed with lymphedema due to progressive limb asymmetry and non-pitting edema [3] .…”
Section: Musculoskeletal Injuriesmentioning
confidence: 99%
See 1 more Smart Citation